(3cJGH GdSjGSIs - (3CHh HcQ eMeO Hf GdMSf GdMVQei GdbQhi GdeQGOis ((3YjSi Hf YHO Gddg Hf eMeO GdYhSLi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi aVjdI GdYbd s
(3BNQgG (B:s
(3aYdjc HgPg GdaVGFd Ef CWdbJgG , hEdG aNO eG CWdbJ efgG aEf CNP Gdbdjd NjQ ef JQc GdLejY ced GdcJGH HMeO Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(627 / 40) s
Keywords: (3GdSjGSI hGdGLJeGYs